PENGARUH NON PERFORMING LOAN (NPL)DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAPLOANTO DEPOSIT RATIO (LDR)PADA PT.BANK RAKYAT INDONESIA (Persero)Tbk - Asriati, Asriati; Ariyati, juhri (Jurnal Ekonomi Balance, 2017)
The objective of this research is to show Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) to Liquidity illustrated through Loan to Deposit Ratio (LDR) at PT. Bank Rakyat Indonesia (Persero), Tbk. partially. The analytical method is Multiple Linear Regression analysis with SPSS version 21 program. Period of observation conducted in this research that is for 5tahun, from 2010 - 2014. The results of this study indicate that the NPL has a negative and insignificant effect on LDR and positive and insignificant CAR of the LDR.